Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery comprising same

By introducing dopant Nb or Ta into the lithium excess layered oxide of the lithium secondary battery, the growth of primary particles is adjusted and a single crystal structure is formed, which solves the problem of low voltage attenuation and filling density of lithium secondary battery during the life cycle, and improves the energy density and structural stability.

CN119905576APending Publication Date: 2025-04-29ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510101013.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-04-27
Filing Date
2020-10-16
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Lithium secondary batteries have problems of low voltage attenuation and low fill density during the life cycle, which affects their commercialization and performance.

Method used

By introducing dopant Nb or Ta into the lithium excess layered oxide, the growth of primary particles is adjusted to form a single crystal structure, thereby improving the internal structural stability and energy density of the positive electrode active material.

Benefits of technology

The energy density of lithium secondary batteries is increased and the specific surface area of ​​particles is reduced, which extends the battery life and reduces the voltage drop problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905576A_ABST
    Figure CN119905576A_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium secondary battery positive electrode active material, a method for preparing the same, and a lithium secondary battery comprising the same. A positive electrode active material for a lithium secondary battery according to the present invention contains a lithium excess layered oxide, and in the lithium excess layered oxide, primary particles having an average particle diameter of 300 nm to 10 [mu] m are contained in an amount of 50-100 vol% relative to the total lithium excess layered oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application number 202011109592.2. The filing date of the original application is October 16, 2020, and the name of the invention is "Lithium secondary battery positive electrode active material, its preparation method and lithium secondary battery containing the same". Technical Field

[0002] The present invention relates to a positive electrode active material comprising an overlithiated layered oxide (OLO), and more particularly to a lithium secondary battery positive electrode active material in which the size of primary particles is adjusted by a dopant that acts as a flux for growing primary particles, a preparation method thereof, and a lithium secondary battery comprising the same. Background Art

[0003] With the development of portable mobile electronic devices such as smart phones, MP3 players, and tablet computers, the demand for secondary batteries that can store electrical energy has increased dramatically. In particular, with the advent of electric vehicles, medium and large energy storage systems, and portable devices that require high energy density, the demand for lithium secondary batteries has increased.

[0004] Recently, the most popular positive electrode active material is lithium nickel manganese cobalt oxide Li (Ni x Co y Mn z )O2 (In this case, the above x, y, and z are the atomic fractions of independent oxide constituent elements, 0<x≤1, 0<y≤1, 0<z≤1, and 0<x+y+z≤1). Compared with LiCoO2, which has been actively studied and used as a positive electrode active material, the above material can be used in a high voltage environment, so it has the advantage of high capacity, and because the Co content is relatively small, it has the advantage of low price. However, there are disadvantages in that the rate capability and life characteristics under high temperature conditions are not good.

[0005] In this regard, efforts are being made to surpass the existing Li(Ni x Co y Mn z )O2, showing a high reversible capacity of lithium-overlayered oxide (OLO), which is suitable for the research of lithium secondary batteries.

[0006] However, there will be a voltage decay phenomenon during the life cycle. This is because during the life cycle, due to the movement of transition metals, the structure changes from spinel-like to cubic. This voltage decay phenomenon must be solved for the commercialization of lithium secondary batteries. In addition, the problem of low packing density also needs to be solved. Summary of the invention

[0007] The purpose of the present invention is as follows: the positive electrode active material for a secondary battery containing a lithium-excess layered oxide according to an embodiment of the present invention regulates the growth of primary particles, thereby increasing the energy density and reducing the specific surface area of ​​the particles compared to existing polycrystalline lithium-excess layered oxides.

[0008] Another object of the present invention is to provide a dopant substance for improving the internal structural stability of positive electrode active material particles.

[0009] The overlithiated layered oxide (OLO) of the embodiment of the present invention is represented by the following chemical formula 1, wherein the primary particles are aggregated to form secondary particles, and among the primary particles constituting the secondary particles, the primary particles with a size of 300 nm to 10 μm occupy 50 volume percent to 100 volume percent.

[0010] Chemical formula 1: rLi2MnO3·(1-r)LiaNi x Co y Mn z M1 1-(x+y+z) O2

[0011] wherein the above 0<r≤0.6, 0<a≤1, 0≤x≤1, 0≤y<1, 0≤z<1 and 0<x+y+z<1, and the above M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B and Bi,

[0012] In the positive electrode active material according to the embodiment of the present invention, the primary particles are irregular, and the size of the primary particles is the longest length.

[0013] In the above-mentioned positive electrode active material of an embodiment of the present invention, the size of the primary particles in the positive electrode active material is increased compared with the size of the primary particles in the precursor step, and the ratio of (the size of the primary particles of the positive electrode active material with added dopants) / (the size of the primary particles of the positive electrode active material without added dopants) is greater than 1, preferably, greater than 50.

[0014] In the positive electrode active material of the embodiment of the present invention, the primary particles having a size of 1 μm to 2 μm may account for 50 to 100 volume percent relative to the entire lithium-excess layered oxide.

[0015] Furthermore, the average particle size of the secondary particles of the positive electrode active material of the embodiment of the present invention may be 2 μm to 20 μm.

[0016] Furthermore, in the positive electrode active material according to the embodiment of the present invention, the M1 in the chemical formula 1 may be a dopant that functions as a flux for growing the primary particles.

[0017] Furthermore, in the positive electrode active material according to the embodiment of the present invention, the M1 in the chemical formula 1 may be at least one selected from Nb, Mo, Ta and W, and the M1 may be Nb or Ta.

[0018] Furthermore, in the positive electrode active material of the embodiment of the present invention, the M1 may be included in an amount of 0.001 mol % to 10 mol % relative to the entire lithium-excess layered oxide.

[0019] Furthermore, in the positive electrode active material of the embodiment of the present invention, the M1 may be Nb, and the Nb may be contained in an amount of 0.1 mol % to 1 mol % relative to the entire lithium-excess layered oxide.

[0020] Furthermore, the positive electrode active material of the embodiment of the present invention may further include a substance represented by the following chemical formula 2:

[0021] Chemical formula 2: Li a M1O b

[0022] Wherein, 0<a≤7, 0<b≤15, M1 is at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta and W. Li in the above chemical formula 2 a M1O b It may be a substance generated by a reaction between a dopant that induces growth between primary particles and lithium.

[0023] Furthermore, in the above-mentioned positive electrode active material of the present invention, as the primary particles grow, when X-ray diffraction analysis is performed, when calcination is performed under the same conditions as the half-value width (FWHM (deg.)) in I(104), after including M1, the half-value width can be reduced at a rate of 5% to 50% compared to the material not containing M1.

[0024] Furthermore, the energy density per unit volume (Wh / L) of the positive electrode active material of the present invention may be 2.7 (Wh / L) to 4.0 (Wh / L).

[0025] Furthermore, the energy density per unit volume (Wh / L) of the positive electrode active material of the present invention can be increased by 5% to 30% compared to a material not containing M1.

[0026] Furthermore, the packing density (g / cc) of the positive electrode active material according to the embodiment of the present invention may be 2.0 (g / cc) to 4.0 (g / cc).

[0027] Moreover, the specific surface area (BET, m 2 / g) can be 0.1 (BET, m 2 / g) to 1.5 (BET, m 2 / g).

[0028] Moreover, as the primary particles grow, the specific surface area (BET, m 2 / g) can be reduced at a rate of 25% to 80%.

[0029] Furthermore, in the positive electrode active material of the embodiment of the present invention, the ratio of the molar number of lithium to the total molar number of metals selected from Ni, Co or Mn (Li / (Ni+Co+Mn)) may be 1.1 to 1.6.

[0030] Furthermore, in the positive electrode active material according to the embodiment of the present invention, the ratio of the molar number of Mn to the total molar number of Ni (Mn / Ni) may be 1 to 4.5.

[0031] Furthermore, the positive electrode active material of the embodiment of the present invention may be a solid solution phase of a mixture of Li2MnO3 with a monoclinic structure and LiMO2 with a rhombohedral structure, and the M may be at least one selected from Ni, Co, Mn, and M1.

[0032] Furthermore, the positive electrode active material according to the embodiment of the present invention may present a plateau based on Li2MnO3 in the 4.4V region of the initial charge-discharge curve.

[0033] The method for preparing the positive active material according to the embodiment of the present invention comprises: preparing a positive active material precursor comprising at least one element selected from Ni, Co and Mn; and mixing a lithium compound and a compound comprising M1 of the chemical formula 1 with the positive active material precursor for calcining.

[0034] In the above-mentioned method for preparing positive electrode active material in an embodiment of the present invention, the size of the primary particles in the positive electrode active material step is increased compared with the size of the primary particles in the precursor step, and the ratio of (the size of the primary particles of the positive electrode active material with added dopants) / (the size of the primary particles of the positive electrode active material without added dopants) is greater than 1, preferably, greater than 50.

[0035] Furthermore, in the method for preparing the positive electrode active material according to the embodiment of the present invention, the temperature of the calcination step may be 750° C. to 950° C.

[0036] Furthermore, in the method for preparing the positive active material of the embodiment of the present invention, after the step of preparing the precursor and before the calcining step, a step of calcining the prepared precursor may be further included, and the temperature of the calcining step may be 300° C. to 600° C.

[0037] Furthermore, in the method for preparing the positive electrode active material according to the embodiment of the present invention, the M1 is Nb, and the compound containing the Nb is Nb2O5.

[0038] Furthermore, in the method for preparing the positive electrode active material according to the embodiment of the present invention, after the calcination step, the method may further include the steps of rinsing and drying the calcined positive electrode active material.

[0039] Furthermore, in the method for preparing the positive electrode active material according to the embodiment of the present invention, after the calcination step, a step of heat treating the calcined positive electrode active material may be further included.

[0040] The secondary battery according to the embodiment of the present invention includes the above-mentioned positive electrode active material.

[0041] The positive electrode active material for secondary batteries comprising lithium-excess layered oxides in an embodiment of the present invention comprises a dopant substance for improving the internal structural stability of the positive electrode active material particles. Compared with the existing polycrystalline lithium-excess layered oxides (OLO), as the primary particles become single crystal, the filling density is improved, and at the same time, the energy density is also improved, and the specific surface area of ​​the particles will be reduced.

[0042] Furthermore, compared with the case of using the existing polycrystalline lithium-excess layered oxide (OLO), in a secondary battery containing the above-mentioned positive electrode active material, as the specific surface area decreases, the surface portion of the positive electrode active material will decrease, so the life and voltage drop problems will be significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The following are scanning electron microscope (SEM) analysis images of the positive electrode active materials of the comparative examples and the examples of the present invention.

[0044] FIG. 2 a and FIG. 2 b are scanning electron microscope analysis images of the cross section of the positive electrode active material of the comparative example and the embodiment of the present invention.

[0045] Figure 3a and Figure 3b The results of energy dispersive X-ray spectroscopy (EDX) analysis of the positive electrode active materials of Comparative Examples and Examples of the present invention are shown.

[0046] Figure 4 and Figure 5 The following are the results of X-ray diffraction (XRD) analysis of the positive electrode active materials of Comparative Examples and Examples of the present invention.

[0047] Figure 6 This is a graph comparing the measurement results of X-ray diffraction (XRD) analysis of positive electrode active materials of Comparative Examples and Examples of the present invention and the half maximum width (FWHM (deg.)) in I(104).

[0048] Figure 7 This is a graph comparing the packing density (g / cc) of the positive electrode active materials of the comparative example and the example of the present invention.

[0049] Figure 8 To compare the specific surface areas (BET, m 2 / g) diagram.

[0050] Fig. 9 This is a graph comparing initial voltage curves of positive electrode active materials according to comparative examples and examples of the present invention.

[0051] Fig.10 This is a graph comparing the energy density per unit volume of the positive electrode active materials of the comparative example and the example of the present invention.

[0052] Fig.11 The graph is a graph comparing the capacity retention of the positive electrode active materials according to the comparative example and the embodiment of the present invention with respect to the cycle number.

[0053] Fig.12 This is a graph comparing the capacity of the positive electrode active materials according to the comparative example and the example of the present invention as a function of the cycle number.

[0054] Fig.13 The graph is a graph comparing the voltage retention of the positive electrode active materials of the comparative example and the embodiment of the present invention with respect to the cycle number.

[0055] Fig.14 The graph is a graph comparing the nominal voltage of the positive electrode active materials according to the comparative example and the example of the present invention with respect to the cycle number. DETAILED DESCRIPTION

[0056] Expressions such as “comprising” used in this specification should be understood as open-ended terms with the possibility of including other embodiments.

[0057] The terms “preferably” and “preferably” used in the present specification refer to embodiments of the present invention that can provide specified advantages under specified conditions, and do not exclude other embodiments from the scope of the present invention.

[0058] Hereinafter, the positive electrode active material according to the embodiment of the present invention will be described in detail.

[0059] The positive electrode active material of the embodiment of the present invention includes lithium-excess layered oxide.

[0060] The above-mentioned lithium-excess layered oxide may be a solid solution phase of a mixture of Li2MnO3 with a monoclinic structure and LiMO2 with a rhombohedral structure, and the above-mentioned M may be at least one selected from Ni, Co, Mn, and M1.

[0061] Furthermore, the lithium-excess layered oxide of the embodiment of the present invention can present a plateau based on Li2MnO3 in the 4.4V region of the initial charge-discharge curve. During the initial charging process, the lithium-excess layered oxide of the embodiment of the present invention is electrochemically inactive relative to lithium up to the 4.4V region, and in the region above 4.4V, it is possible to cause lithium separation reaction and oxidation reaction (oxygen evolution) in the Li2MnO3 phase.

[0062] The lithium-excess layered oxide according to an embodiment of the present invention is represented by the following Chemical Formula 1.

[0063] Chemical formula 1: rLi2MnO3·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O2

[0064] wherein the above 0<r≤0.6, 0<a≤1, 0≤x≤1, 0≤y<1, 0≤z<1 and 0<x+y+z<1, and the above M1 is at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B and Bi,

[0065] The ratio of the molar number of lithium to the total molar number of metal selected from Ni, Co or Mn (Li / (Ni+Co+Mn)) may be 1.1 to 1.6.

[0066] In the lithium-excess layered oxide represented by the above Chemical Formula 1, a ratio of lithium moles (Li / Ni+Co+Mn) relative to the total moles contained in Ni, Co or Mn may be 1.1 to 1.6, 1.2 to 1.6, 1.2 to 1.5, 1.2 to 1.4 or 1.2 to 1.3.

[0067] In the above Chemical Formula 1, the value of the above x may be greater than 0 to 0.5, greater than 0 to 0.4, greater than 0 to 0.3, greater than 0 to 0.2, or greater than 0 to 0.1.

[0068] In the above Chemical Formula 1, the value of y may be greater than 0 to 0.5, greater than 0 to 0.4, greater than 0 to 0.3, greater than 0 to 0.2, or greater than 0.1 to 0.2.

[0069] Also, the ratio of the molar number of Mn relative to the total molar number of Ni (Mn / Ni) may be 1 to 4.5, 1 to 4, 2 to 4.5, 2 to 4, 3 to 4.5, or 3 to 4.

[0070] The positive electrode active material of the present invention is a lithium-rich and manganese-rich oxide, and the density and voltage drop problems can be more effectively improved by adjusting the content of Mn and Li and the ratio of the grain boundary density to a predetermined range.

[0071] The oxide of the present invention has a layered structure, and lithium atomic layers and metal atomic layers of Ni, Co, Mn or M1 can form an alternately stacked layered structure via oxygen atomic layers.

[0072] The surface of the layer forming the layered structure of the above-mentioned positive electrode active material can have a crystal orientation along the direction perpendicular to the C-axis. In this case, the mobility of the lithium ions contained in the above-mentioned positive electrode active material is improved, and the structural stability of the above-mentioned positive electrode active material is increased. When applicable to batteries, the initial capacity characteristics, output characteristics, resistance characteristics and long-term life characteristics can be improved.

[0073] Furthermore, as an example, the positive electrode active material including the above-mentioned lithium-excess layered oxide of the present invention may have a single-crystal structure.

[0074] In the positive electrode active material of the embodiment of the present invention, the primary particles may be aggregated to form secondary particles, and the size of the primary particles may be 0.01 μm to 10 μm.

[0075] Moreover, in the positive electrode active material of the embodiment of the present invention, among the primary particles constituting the secondary particles, the primary particles with a size of 300 nm to 5 μm may occupy 50 volume percent to 100 volume percent, 70 volume percent to 100 volume percent or 100 volume percent.

[0076] Moreover, in the positive electrode active material of the embodiment of the present invention, among the primary particles constituting the secondary particles, the primary particles with a size of 300 nm to 10 μm may occupy 50 volume percent to 100 volume percent, 70 volume percent to 100 volume percent or 100 volume percent.

[0077] Furthermore, as an example, in the positive electrode active material, among the primary particles constituting the secondary particles, the primary particles having a size of 500 nm to 10 μm may occupy 50 volume percent to 100 volume percent, 70 volume percent to 100 volume percent, or 100 volume percent.

[0078] Furthermore, as an example, in the positive electrode active material, the content of primary particles having a size of 1 μm to 2 μm may be 50% to 100% relative to the entire primary particles constituting the secondary particles.

[0079] Furthermore, as an example, in the positive electrode active material, primary particles having a size of 1 μm to 10 μm may account for 50 volume percent to 100 volume percent, 70 volume percent to 100 volume percent, or 100 volume percent of the entire lithium-excess layered oxide.

[0080] Furthermore, as an example, in the positive electrode active material, primary particles having a size larger than 1 μm may account for 50 volume percent to 100 volume percent, 70 volume percent to 100 volume percent, or 100 volume percent relative to the entire lithium-excess layered oxide.

[0081] Furthermore, as an example, in the positive electrode active material, primary particles having a size of 2 μm or more may account for less than 50 volume percent to 100 volume percent or 50 volume percent to 70 volume percent of the entire lithium-excess layered oxide.

[0082] The size of the primary particle mentioned above is the longest length of the particle.

[0083] In addition, as an example, the average particle size of the primary particles of the positive electrode active material may be greater than 500 nm to 10 μm or 1 μm to 10 μm.

[0084] In the particle size distribution curve of particles, the average particle size of the present invention can be defined as the particle size corresponding to 50% of the cumulative volume. For example, the average particle size can be measured using a laser diffraction method.

[0085] The present invention increases the primary particle size in the lithium-excess layered oxide to have a single crystal structure, and when calcined under the same conditions, when an X-ray diffraction analysis is performed, the half value width (FWHM (deg.)) in I (104) can be reduced by 5% to 25%, 5% to 20%, 10% to 25%, or 10% to 20% compared to a comparative example not containing M1,

[0086] Furthermore, the positive electrode active material of the present invention has a single crystal structure by increasing the primary particle size in the lithium-excess layered oxide, and when M1 is included, the energy density per unit volume (Wh / L) can be increased at a ratio of 5% to 25%, 5% to 20%, 10% to 25% or 10% to 20% compared to the comparative example not including M1.

[0087] Furthermore, the positive electrode active material of the present invention has a single crystal structure by increasing the primary particle size in the above-mentioned lithium-excess layered oxide, and the specific surface area (BET, m 2 / g) can be reduced at a rate of 20% to 80%.

[0088] Existing lithium-excess layered oxides have a problem of voltage drop during rotation. The voltage drop is caused by the transition from a spinel-like structure to a cubic structure during the cycle due to the movement of transition metals. This phenomenon mainly occurs on the surface of the positive electrode active material. The present invention can make the positive electrode active material have a single crystal by inducing the growth of the above-mentioned primary particles, thereby increasing the energy density per unit volume and reducing the specific surface area. As a result, as the surface of the positive electrode active material is reduced, the problems of life and voltage drop can be solved. In the present invention, the content of inducing the growth of the above-mentioned primary particles is included in the concepts of nucleation, ostwald ripening, and particle aggregation.

[0089] In addition, the reduction in specific surface area can solve the problem of side reactions with the electrolyte.

[0090] In the positive electrode active material of the present invention, the more parts corresponding to the single crystal structure there are, the more the voltage drop problem that occurs in polycrystals can be improved.

[0091] The positive electrode active material of the present invention comprises M1 of the above chemical formula 1 as a dopant that induces growth between primary particles. More preferably, the above M1 is a dopant that acts as a flux that induces growth between primary particles of the above lithium-excess layered oxide, and can be applied to the lattice structure. As one embodiment, in the calcination step with the lithium compound, the flux dopant is added and mixed to perform heat treatment together, thereby increasing the size of the primary particles. Acting as a flux refers to the role of a dopant that can increase the size of the primary particles by growth between the primary particles.

[0092] The above-mentioned M1 can be at least one selected from Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Mg, Gd, Sm, Ca, Ce, Fe, Al, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S, B and Bi. More preferably, it can be at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta and W that can further grow the size of the primary particles to more appropriately adjust to a specific range. Most preferably, it can be at least one selected from Nb and Ta.

[0093] In the positive electrode active material of the present invention, when the dopant element that induces growth between the primary particles is mixed with the lithium compound in the calcination step and heat-treated together, the problems of life and voltage drop can be improved as the surface of the positive electrode active material is reduced.

[0094] The positive electrode active material of the present invention can contain the dopant element uniformly on the surface and inside of the positive electrode active material, thereby improving the structural stability of the positive electrode active material, and improving the life characteristics and thermal stability.

[0095] In the positive electrode active material of the present invention, the M1 may include 0.01 mol% to 3 mol% relative to the lithium-excess layered oxide as a whole. In addition, it may include 0.1 mol% to 2 mol%, and more preferably, it may include 0.1 mol% to 1 mol%. When the dopant M1 included in the flux for inducing the growth of primary particles exceeds the above range, an excessive amount of lithium composite oxide is formed, which may lead to a decrease in capacity and efficiency. When it is less than the above range, the effect of growing primary particles is negligible.

[0096] In addition, the secondary battery positive electrode active material according to the embodiment of the present invention may further include a lithium-excess layered oxide represented by the following Chemical Formula 2.

[0097] Chemical formula 2: Li a M1O b

[0098] Among them, the above-mentioned 0<a≤7, 0<b≤15, and M1 is at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta and W.

[0099] Li in the above chemical formula 2 a M1O b It may be a substance generated by a reaction between a dopant that induces growth between primary particles and lithium.

[0100] When the X-ray diffraction analysis of the positive active material of the embodiment of the present invention is performed, the half-value width (FWHM (deg.)) in I (104) can be 0.1 (deg.) to 0.25 (deg.), and the above value can be changed according to the manganese content. In this regard, the reduction rate of the half-value width can be adjusted by adding the above-mentioned dopant M1 and adjusting the content, thereby solving the problem of life and voltage drop.

[0101] Furthermore, the energy density (Wh / L) per unit volume of the positive electrode active material of one embodiment that can be adjusted by adding the dopant M1 and adjusting the content thereof can be 2.7 (Wh / L) to 4.0 (Wh / L).

[0102] Furthermore, the specific surface area (BET, m 2 / g) can be 0.01 (BET, m2 / g) to 2 (BET, m2 / g).

[0103] The average particle size of the positive electrode active material particles in the embodiment of the present invention may be 0.1 μm to 30 μm, 0.1 μm to 25 μm, 0.1 μm to 20 μm, 0.1 μm to 15 μm or 0.1 μm to 10 μm.

[0104] The positive electrode active material including the lithium-excess layered oxide according to the embodiment of the present invention may have a structure in which secondary particles are formed by growth of primary particles.

[0105] Furthermore, the positive electrode active material particles may be in the form of fibers, films or spheres, and more preferably, may be in the form of spheres.

[0106] In the present specification, in the particle size distribution curve of particles, the average particle size may be defined as the particle size corresponding to 50% of the cumulative volume. For example, the average particle size may be measured using a laser diffraction method.

[0107] Furthermore, the shape of the primary particles may be a rod, a plate, a spherical, an ellipse, a disk or an amorphous shape. Preferably, the shape of the primary particles may be at least one of a plate or an amorphous shape.

[0108] In the positive electrode active material of the embodiment of the present invention, the size of the primary particles can be adjusted, and the number of the primary particles inside the secondary particles can reach 1 to 10,000, 1 to 1,000, 1 to 100, and 1 to 10.

[0109] The positive electrode active material according to the embodiment of the present invention may further include a coating layer.

[0110] The above-mentioned coating may include one or more coating materials selected from P, Nb, Si, Sn, Al, Pr, Al, Ti, Zr, Fe, Al, Fe, Co, Ca, Mn, Ti, Sm, Zr, Fe, La, Ce, Pr, Mg, Bi, Li, W, Co, Zr, B, Ba, F, K, Na, V, Ge, Ga, As, Sr, Y, Ta, Cr, Mo, W, Mn, Ir, Ni, Zn, In, Na, K, Rb, Cs, Fr, Sc, Cu, Ru, Rh, Pd, Ag, Cd, Sb, Hf, Ta, Re, Os, Pt, Au, Pb, Bi and Po.

[0111] The coating layer can suppress the occurrence of side reactions by preventing the positive electrode active material from contacting with the electrolyte in the lithium secondary battery, thereby improving life characteristics and increasing the packing density, and the coating layer can function as a lithium ion conductor.

[0112] Furthermore, the coating layer may be formed between grain boundaries of the primary particles.

[0113] Furthermore, the coating layer may have a thickness of 0.1 nm to 500 nm.

[0114] The coating layer may be formed on the entire surface of the positive electrode active material, or may be formed on a portion of the surface.

[0115] Furthermore, the coating may be in the form of a single-layer coating, a double-layer coating, a grain boundary coating, a uniform coating or an island coating.

[0116] In the positive electrode active material comprising the above-mentioned lithium-excess layered oxide of an embodiment of the present invention, the above-mentioned positive electrode active material may include a concentration gradient portion, and the concentration of at least one of the above-mentioned Ni, Co, Mn and M1 presents a concentration gradient inside and outside the particles of the positive electrode active material, that is, inside and outside the secondary particles and at least a part of the inside and outside of the primary particles.

[0117] In the positive electrode active material according to the embodiment of the present invention, a lithium ion diffusion path may be formed inside the primary particles.

[0118] In the positive electrode active material of the embodiment of the present invention, the surface of the layer forming the above-mentioned layered structure can have a crystal orientation along the direction perpendicular to the C axis within the primary particle, and form a lithium ion migration path along the center direction of the positive electrode active material particle inside or outside the primary particle.

[0119] Hereinafter, a method for preparing a positive electrode active material according to an embodiment of the present invention will be described in detail.

[0120] The method for preparing the positive electrode active material for a secondary battery according to an embodiment of the present invention includes the following steps, namely, preparing a positive electrode active material precursor containing at least one element selected from Ni, Co and Mn.

[0121] In order to prepare the above-mentioned precursors, as raw materials for nickel, cobalt, manganese and dopants, sulfates, nitrates, acetates, halides, hydroxides or hydroxy oxides containing each of the above-mentioned metal elements can be used. There is no limitation as long as they can be dissolved in solvents such as water.

[0122] Furthermore, in order to prepare the above-mentioned precursor, co-precipitation, spray-drying, a solid phase method, wet milling, a fluidized bed drying method, and a vibration drying method may be performed.

[0123] The method for preparing the positive active material for secondary battery of the embodiment of the present invention performs the following steps, namely, mixing the lithium compound as the precursor of the prepared positive active material and the compound M1 of the chemical formula 1 as the dopant contained in the growth flux between primary particles and calcining.

[0124] In the present invention, in the calcination step with the lithium compound, the dopant M1 and the solder resist contained in the flux for inducing the growth between the primary particles can be added, thereby reducing the surface of the positive electrode active material as the primary particles grow, and solving the problems of life and voltage reduction.

[0125] In the method for preparing a positive electrode active material for a secondary battery of the present invention, the lithium compound may be lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide or oxyhydroxide, but is not limited thereto.

[0126] Furthermore, the temperature of the calcining step may be 750°C to 950°C, 800°C to 950°C, or 850°C to 950°C.

[0127] Furthermore, after the step of preparing the above-mentioned precursor and before the calcination step described below, a step of calcining the prepared precursor may be included. The temperature of the calcination step may be 300°C to 600°C, 400°C to 600°C, or 500°C to 600°C.

[0128] The step of calcining the precursor may be performed by repeating the temperature increase and maintenance, or may be performed in the order of temperature increase, maintenance, cooling, re-temperature increase, maintenance and cooling.

[0129] Furthermore, after the calcination step, the method may further include the steps of rinsing and drying the calcined positive electrode active material.

[0130] Furthermore, after the above steps, a step of forming a coating inside or outside the positive electrode active material may be included, and the coating may be formed by dry coating, wet coating, CVD coating or ALD coating. However, the coating method is not particularly limited as long as the coating can be formed on a part of the positive electrode active material.

[0131] The preparation method of the positive electrode active material can be applied to the contents described above for the positive electrode active material.

[0132] The secondary battery according to the embodiment of the present invention includes the above-mentioned positive electrode active material.

[0133] The positive electrode active material is as described above, and the binder, conductive material and solvent are not particularly limited as long as they can be used in secondary batteries and positive electrode collectors.

[0134] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode faces the positive electrode, and the electrolyte is formed between the positive electrode and the negative electrode. As long as the battery can be used as a secondary battery, it is not particularly limited.

[0135] The present invention will be described in more detail below by way of examples, but the scope of the present invention is not limited to these examples.

[0136] Example 1. Preparation of positive electrode active material

[0137] synthesis

[0138] Spherical Ni was synthesized by co-precipitation method. 0.2 Co 0. 1Mn 0.7 CO3 precursor.

[0139] In a 90L reactor, 25 weight percent NaCO3 and 28 weight percent NH4OH are added to a 2.5M aqueous solution of composite transition metal sulfuric acid mixed with NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in a mole ratio of 20:10:70. In this case, the pH in the reactor is maintained at 8.0 to 11.0 and the temperature is maintained at 45°C to 50°C. In addition, N2 is added to the reactor as an inert gas to prevent oxidation of the prepared precursor. After the synthesis stirring is completed, a filter press (Filter Press, F / P) device is used for washing and dehydration. Finally, the dehydrated product is dried at a temperature of 120°C for 2 days and filtered through a 75μm (200Mesh) sieve to obtain 4μm to 20μm Ni 0.2 Co 0.1 Mn 0.7 CO3 precursor.

[0140] Roasting

[0141] In a Box calcining furnace, the prepared precursor is maintained under an O2 or Air (50 L / min) environment, and the temperature is increased by 2°C per minute to maintain the temperature at 550°C for 1 hour to 6 hours, followed by furnace cooling.

[0142] Calcination

[0143] For the above-mentioned calcined precursor, LiOH or Li2CO3 is weighed so that the Li / (Ni+Co+Mn) ratio reaches 1.45, and 0.3 mol% of Nb2O5 is weighed as a flux dopant (Flux dopant) to induce growth between primary particles and mixed using a manual mixer (MM).

[0144] In a Box calcining furnace, the mixture is maintained under O2 or Air (50L / min) exchange, the temperature is increased by 2°C per minute, and the calcination temperature is maintained at 900°C for 7 to 12 hours, followed by furnace cooling to prepare the positive electrode active material.

[0145] The composition of the positive electrode active material prepared in Example 1 is Li:Ni:Co:Mn:Nb=15.3:15.1:9.3:59.8:0.4 (wt %).

[0146] Example 2. Preparation of positive electrode active material

[0147] The positive electrode active material was prepared by the same method as in Example 1, except that 0.6 mol % of Nb 2 O 5 was mixed as a flux dopant in the calcination step of Example 1.

[0148] The composition of the positive electrode active material prepared in Example 2 is Li:Ni:Co:Mn:Nb=15.0:14.8:9.3:60.0:0.8 (wt %).

[0149] Comparative Example 1. Preparation of positive electrode active material

[0150] A positive electrode active material was prepared by the same method as in Example 1, except that Nb 2 O 5 was not mixed as a flux dopant in the calcination step of Example 1.

[0151] Comparative Example 2. Preparation of positive electrode active material

[0152] In the calcination step of the above-mentioned Example 2, a positive electrode active material was prepared by the same method as that of the above-mentioned Example 2, except that ammoniumniobate oxalate (C4H4NNbO9xH2O) was mixed as a flux dopant.

[0153] Experimental Example: Scanning electron microscopy measurement

[0154] The positive electrode active materials prepared in the above-mentioned embodiments and comparative examples were measured by scanning electron microscopy, and the results are presented in Figure 1 middle.

[0155] according to Figure 1 It can be confirmed that the size of the primary particles of the positive electrode active material of the above embodiment is increased compared with Comparative Example 1, by increasing the amount of Nb2O5 added as a flux dopant that induces growth between the primary particles.

[0156] In the case of the positive electrode active material prepared by the example of the present invention, the size of the primary particles is 300 nm to 5 μm, and it can be confirmed that the primary particles can be adjusted to sub-micron size, rather than the conventional nano-size primary particles.

[0157] In the case of Comparative Example 2, the Nb compound was added at the same 0.6 mol %, but the Nb compound used in Comparative Example 1 was different, so it was confirmed that the particle size was smaller than that of Example 1 in which Nb was added at a smaller amount of 0.3 mol %.

[0158] Experimental example: Cross-section scanning electron microscopy measurement

[0159] The cross sections of the positive electrode active materials prepared in the above-mentioned examples and comparative examples were measured by scanning electron microscopy, and the results are presented in FIG. 2 a and FIG. 2 b .

[0160] 2a is a scanning electron microscope image of a cross section of the positive electrode active material prepared in Comparative Example 1, which can confirm the primary particles existing outside the secondary particles of the positive electrode active material and the size of the primary particles existing inside the secondary particles.

[0161] In contrast, FIG2b is a cross-sectional scanning electron microscope image of the positive electrode active material prepared in Example 2, which can confirm the primary particles existing outside the secondary particles of the positive electrode active material and the growth of the size of the primary particles existing inside the secondary particles.

[0162] Experimental example: Energy dispersive X-ray spectrometer measurement

[0163] The energy dispersive X-ray spectrometer photographs of the positive electrode active materials prepared in the above-mentioned embodiments and comparative examples are measured, and the results are presented in Figure 3a and Figure 3b middle.

[0164] according to Figure 3a , showing the energy dispersive X-ray spectrometer results of the positive electrode active material to which the flux dopant prepared in the above-mentioned Example 2 is added, it can be confirmed that Ni, Co and Mn are uniformly contained in the particles and Nb added as a flux dopant (Flux dopant) to induce growth between primary particles.

[0165] Figure 3b The results of energy dispersive X-ray spectroscopy of the positive electrode active material to which the flux dopant prepared in Comparative Example 1 was not added were shown, and it was confirmed that only Ni, Co, and Mn elements were uniformly contained in the particles.

[0166] Experimental Example: X-ray diffraction analysis

[0167] The X-ray diffraction analysis results of the positive electrode active material prepared in the embodiments or comparative examples of the present invention are shown in Figures 4 to 6 X-ray diffraction analysis wavelength used.

[0168] exist Figure 4 In the case of adding a flux dopant, it can be confirmed that when performing X-ray diffraction analysis, the major peak I (003) of the lithium-excess layered oxide shifts at a low angle. This may be evidence that Nb, a flux dopant, is coated into the lithium-excess layered oxide lattice.

[0169] exist Figure 5 It can be confirmed that when Nb is mixed in Example 2 of the present invention, a peak based on Li3NbO4 appears in the X-ray diffraction analysis.

[0170] exist Figure 6 It can be confirmed that when the X-ray diffraction analysis of the positive electrode active material of the above-mentioned embodiment is performed, the half-value width (FWHM (deg.)) in I(104) is reduced compared with the comparative example, and the half-value width decreases as the content of the flux dopant (Flux dopant) that induces the growth between the primary particles increases.

[0171] More specifically, it was confirmed that the flux dopant, which is a flux dopant that induces growth between primary particles, was adjusted to a reduction rate of 7.5% by adding 0.3 mol % of Nb, and to a reduction rate of 17.3% by adding 0.6 mol %. Even when calcining is performed under the same temperature conditions, the size of the primary particles can be adjusted by adding the dopant, and then the half-value width in I(104) can be adjusted.

[0172] Experimental Example: Packing density measurement

[0173] according to Figure 7It can be confirmed that the packing density (packing density, g / cc) of the positive electrode active material of the above embodiment is increased compared with the above comparative example, and the packing density (packing density, g / cc) increases as the content of the flux dopant increases.

[0174] Experimental Example: Specific surface area determination

[0175] according to Figure 8 It can be confirmed that the specific surface area (BET, m 2 / g) decreases, the more the content of flux dopant increases, the specific surface area (BET, m 2 More specifically, it was confirmed that when 0.3 mol % of Nb was added as a flux dopant, the specific surface area (BET, m 2 / g) is reduced by 60%. If 0.6 mol% is added, the specific surface area (BET, m 2 / g) is reduced by more than 80%.

[0176] Experimental Example: Determination of electrochemical characteristics

[0177] according to Fig. 9 In the case of an embodiment in which a flux dopant inducing the growth of primary particles is added in a prescribed step, compared to other comparative examples, an increase in the initial charge and discharge capacity of a positive electrode active material comprising a lithium-excess layered oxide will increase inter-slabs through the flux dopant, and, with the presence of an ion conductor coating, the kinetics of lithium ions are increased.

[0178] according to Fig.10 It can be confirmed that the energy density per unit volume (Wh / L) of the positive electrode active material of the above embodiment increases compared with the comparative example, and the more the content of the flux dopant increases, the higher the energy density (Wh / L) increases. More specifically, it can be confirmed that the increase rate is adjusted to 9.1% by adding 0.3 mol% of Nb as a flux dopant, and the increase rate is adjusted to 14.9% by adding 0.6 mol%.

[0179] according to Fig.11It can be confirmed that, compared with other comparative examples, in the case of the embodiment in which a flux dopant is added in the calcination step, the piezoelectric characteristics are excellent, and the capacity retention based on the cycle number is maintained as the content of the flux dopant increases.

[0180] according to Fig.12 It can be confirmed that, compared with other comparative examples, in the case of the embodiment in which a flux dopant is added in the calcination step, the voltage characteristic is excellent, and the capacity based on the cycle number is maintained as the content of the flux dopant increases.

[0181] according to Fig.13 It can be confirmed that, compared with other comparative examples, in the case of the embodiment in which a flux dopant is added in the calcination step, the piezoelectric characteristics are excellent, and the voltage retention based on the cycle number is maintained as the content of the flux dopant increases.

[0182] according to Fig.14 It can be confirmed that compared with other comparative examples, in the case of the embodiment in which a flux dopant is added in the calcination step, the piezoelectric characteristics are excellent, and the nominal voltage based on the cycle number is maintained as the content of the flux dopant increases.

[0183] The above experimental results are presented in Table 1 below.

[0184] Table 1

[0185]

Claims

1. A positive electrode active material for a secondary battery, comprising a lithium-excess layered oxide, characterized in that: It is represented by the following chemical formula 1: Chemical formula 1: rLi2MnO3·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O2 In the chemical formula 1, 0<r≤0.6, 0<a≤1, 0≤x≤1, 0≤y<1, 0≤z<1 and 0<x+y+z<1, and M1 is at least one selected from the group consisting of Na, K, Mg, Al, Fe, Cr, Y, Sn, Ti, B, P, Zr, Ru, Nb, W, Ba, Sr, La, Ga, Gd, Sm, Ca, Ce, Ta, Mo, Sc, V, Zn, Nb, Cu, In, S and Bi, The primary particles are aggregated to form secondary particles, wherein the primary particles having a size of 300 nm to 10 μm account for 50 volume percent to 100 volume percent of the primary particles constituting the secondary particles. wherein M1 is contained in an amount of 0.01 mol % to 1 mol % relative to the total amount of the above-mentioned lithium-excess layered oxide, The BET specific surface area of ​​the positive electrode active material is 0.1 m 2 / g to 1.5m 2 / g.

2. The positive electrode active material for secondary battery according to claim 1, characterized in that The average particle size of the secondary particles in the positive electrode active material is 2 μm to 20 μm.

3. The positive electrode active material for a secondary battery according to claim 1, characterized in that The M1 in the chemical formula 1 is a dopant that functions as a flux for growing the primary particles.

4. The positive electrode active material for secondary battery according to claim 3, characterized in that: The M1 in the chemical formula 1 is at least one selected from the group consisting of Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta, and W.

5. The positive electrode active material for secondary battery according to claim 1, characterized in that The above-mentioned lithium-excess layered oxide further includes a substance represented by the following Chemical Formula 2: Chemical formula 2: Li a M1O b In the above chemical formula 2, 0<a≤7, 0<b≤15, and M1 is at least one selected from Ba, Sr, B, P, Y, Zr, Nb, Mo, Ta and W.

6. The positive electrode active material for secondary battery according to claim 1, characterized in that When the positive electrode active material is subjected to X-ray diffraction analysis, the half value width in I(104) is reduced by 5% to 50% compared to a material not containing the M1.

7. The positive electrode active material for a secondary battery according to claim 1, characterized in that: The energy density per unit volume (Wh / L) of the positive electrode active material is increased by 5% to 30% compared to a material not containing the M1.

8. The positive electrode active material for secondary battery according to claim 1, characterized in that The packing density of the positive electrode active material is 2.0 g / cc to 4.0 g / cc.

9. A method for preparing a positive electrode active material for a secondary battery according to claim 1, characterized in that: include: A step of preparing a positive electrode active material precursor containing at least one element selected from Ni, Co and Mn; as well as A step of mixing a lithium compound and a compound including M1 of the chemical formula 1 with the positive electrode active material precursor and calcining the mixture.

10. The method for preparing a positive electrode active material for a secondary battery according to claim 9, characterized in that: After the step of preparing the above precursor and before the calcining step, the method further comprises the step of calcining the prepared precursor at a temperature of 300 to 600°C.

11. A secondary battery, characterized in that: Contains the positive electrode active material for secondary battery according to claim 1.